2021
DOI: 10.3390/healthcare9020132
|View full text |Cite
|
Sign up to set email alerts
|

Familial and Parental Predictors of Physical Activity in Late Adolescence: Prospective Analysis over a Two-Year Period

Abstract: Children’s health behaviors are highly influenced by their parents and family. This study aimed to prospectively evaluate the parental/familial factors associated with physical activity levels (PALs) among older adolescents. The participants were 766 adolescents, who were prospectively observed at baseline (when they were 16 years of age), at first follow-up measurement (FU1; 17 years of age), and second follow-up measurement (FU2; 18 years of age). Sociodemographic factors (age, gender, socioeconomic status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…In other words, there is no evidence that a specific age only should be considered "critical" in terms of a more rapid decline in PALs. [9]. The results showed that the relationship between perceived parental support and physical activity enjoyment is mediated by the overweight and obese adolescents' perceived cardiorespiratory fitness and flexibility.…”
Section: Discussionmentioning
confidence: 87%
“…In other words, there is no evidence that a specific age only should be considered "critical" in terms of a more rapid decline in PALs. [9]. The results showed that the relationship between perceived parental support and physical activity enjoyment is mediated by the overweight and obese adolescents' perceived cardiorespiratory fitness and flexibility.…”
Section: Discussionmentioning
confidence: 87%
“…The association between low levels of physical activity and an increased use of new technologies, and, consequently, the increased time spent by children in front of a screen, cannot be understood without considering the current society, which is increasingly affected by circumstances that constantly pose new and different threats to well-being in general and to children in particular [ 63 ]. Faced with this contextual scenario, it is important to consider the greatest possible involvement of parents and teachers to promote the reduction and adequacy of exposure to the computer screen, in an era where the use of digital technology is so integrated [ 47 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies regularly confirm the positive preventive and therapeutic effects of increased PA on many chronic diseases, such as cardiovascular and tumour diseases [3,4]. Therefore, increase in PA is recognised as a worldwide public health priority [5][6][7]. Nowadays, increase in PA activity is most commonly associated with the inclusion of a certain type of physical exercise (PE) in the individuals' daily rhythm.…”
Section: Introductionmentioning
confidence: 99%